FORECASTS FOR THE ECONOMY OF UZBEKISTAN - Mansurov, Shahzod (Science technology&Digital finance, 2023)
In this article, you will find information about the economy of Uzbekistan, "Forecasts on the economy of Uzbekistan", "Tasks and goals for the development of the economy of Uzbekistan", "International Monetary Fund, International Monetary Fund, World You can find answers to questions such as "Opinions and opinions of Bank experts on the development of the economy of Uzbekistan". Also, in the article, which aspects of the economy should be used in our republic, the priority directions of development based on the analysis of their possibilities are defined. Also, by studying, systematizing and generalizing the existing practice in drawing up scientifically based conclusions on the introduction of developed foreign experiences in the economy, suggestions are made not only on how they will take an important place in various fields and in what form they will be introduced.